Pengaruh waktu milling terhadap ukuran butir quartz dari Nagari Saruaso Kabupaten Tanah Datar - Yuni Zahara (Department of Physics – Universitas Negeri Padang UNP, 2016)
Indonesia is a country with abundant natural resources, one of which is the mineral silica material. Silica can have a high value in the world steel industry by changing the quality of the nanomaterial. The method can be implemented in the manufacture of nanomaterial one of which is the High Energy Milling 3D Motion. The purpose of this study was to investigate the influence of milling time on the nanostructure in the form of quartz crystal structure, crystal size, grain size, and morphology. The results showed that for the time milling 6, 12, 24 hours and 30 hours obtained the crystal structure of Hexagonal. Effect of milling time to 6 hours, 12 hours, 24 hours and 30 hours in getting the sample size quartz crystal at around 164 nm, 123 nm, 79 nm, and 68 nm. The grain size in a row is equal to 464 nm, 380 nm, 345 nm, and 293 nm. Morphology homogenous evenly across the surface